Development of Methodology for Characterization of Roll and Pitch Damping Behaviour in a Commercial Vehicle - Sharma, Rupin (My University, 2019)
Vehicle dynamics have been studied by many researchers for the purpose of enhancing passenger comfort in a vehicle. Studies have been conducted into varying suspension parameters and tuning suspension characteristics so as to maximize the passenger’s comfort. In this study, a methodology for characterization of vehicle’s rolling and pitching damping behaviour and for the evaluation of comfort values of roll and pitch characteristics of a vehicle during dynamic maneuvers have been proposed and validated. Several characterization tests, namely, Step Input, Double Lane Change, Straight Line, Dive, Squat, Single Speed Bump and Start Stay Stop Test which simulate several real life driving maneuvers performed by real life driver have been performed on several test vehicles and output parameters such as roll angle, pitch angle, roll rate and pitch rate have been captured and analysed. Subjective Ratings of driver and co-driver are also taken immediately after the maneuvers. After analyzing and tabulation of the output parameters data obtained from characterization tests, correlation between subjective ratings and objective vehicle output data is established. Upon correlation, characterization test is validated and output data is used for evaluation of roll and pitch comfort values for various dynamic maneuvers and objective characterization of vehicle’s roll and pitch damping behaviour.
Keywords: Rolling; Pitching; Yawing; Damping